Formulasi Dan Uji Mutu Fisik Sediaan Foot Lotion Ekstrak Etanol Daun Sirih (Piper bettle L.) Dengan Variasi Konsentrasi Asam Stearat - Juliadi, Debby; Juanita, Rr Asih; Dewi Agustini, Ni Putu (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
Betel leaf extract (Piper bettle L.) is known to contain flavonoid compounds that have antibacterial activity. Betel leaf extract needs to be formulated as a foot preparation lotion to increase the comfort of use as a topical antibacterial. The composition of the emulsifier influences the physical stability of the preparation foot lotion used. This study aims to determine the variation of stearic acid preparations foot lotion, which has good physical quality and is stable in storage. This research is purely experimental laboratory research that aims at development (development), namely developing something in an existing field (development of test methods, drug formulation). The observed responses were the physical quality of the preparations, which included organoleptic tests, homogeneity tests, pH tests, spreadability tests, and adhesion tests. The physical quality of preparations of foot lotion was analyzed descriptively. This research began with a maceration process using 70% ethanol to obtain a thick betel leaf extract (Piper bettle L.). This study made three preparation formulas with foot lotion with stearic acid concentrations of 10%, 12.5%, and 15%. The preparations that have been made are then tested for their physical quality and stability during four weeks of storage. The results of this study indicate that the preparations obtained foot lotion betel leaf ethanol extract (Piper bettle L.) with a variation of stearic acid of 10% to produce preparations of foot lotion with good physical quality seen from organoleptic tests, homogeneity, pH, spreadability, and adhesion and stable in storage for four weeks.